Produtividade de minicepas e enraizamento de miniestacas de Eucalyptus spp. cultivadas em diferentes manejos de minijardim clonal - Somavilla, Luiza Michelon (2020)
The Eucalyptus genus is widely planted in Brazil and the implantation of new peoples requires a lot of quantity and quality. The use of estimation on the clonal mini-garden (CMG) promotes changes in the microenvironment, such as increased temperature and capture, and, consequently, increased research on mini-stumps improving the quality of the produced mini-cuttings. The objective of the study was to evaluate the influence of the use of the equipment during the winter season, the morphology and physiology of the mini-stumps, the survival and rooting of the mini-cuttings and the quality of the seedlings produced. The study was carried out in winter / 2018, at Horto Florestal Barba Negra, in the state of Rio Grande do Sul. The experiment was conducted in the design of surrounding blocks, in a split plot scheme, with two types of mini-garden management in the main plot (with and without mini-tunnels) and three clones in the subplots, with six replications of 72 strains, arranged in a space of 10 cm x 11 cm and configurations in the 8 x 9 configuration, totaling 432 mini-stumps per treatment. The CMG consisted of three clones: E. saligna, E. dunnii and E. urophylla x E. globulus (E. uroglobulus). The morphological, physiological and control attributes of mini-stumps, as well as the environmental factors applied in two MJCs. An assessment of the survival and improvement of the mini-cuttings was carried out on the materials used in both environments. The morphological attributes of the changes were also taxed up to 90 days after establishment. The data were submitted to analysis of variance, considering two factors: management of the CMG and clones. Additionally, an a principal component analysis (PCA) is carried out in order to find the weights of each variable to maximize the variation between the sampling points. The use of mini-tunnels in CMG with estimated increase in temperature, relative reduction in area and deficit of water vapor saturation. But also, higher content of chlorophyll a, reduction in the production of hydrogen (H2O2) and activity of the enzyme guaiacol peroxidase (POD). As CMG mini-stumps with mini-tunnels higher estimated values for electron transport (ETRm) and effective yield of photosystem II (Y (II)), attributes that are directly related to rooting, as demonstrated by the PCA. The evaluation and survival were indifferent to the presence of stocks, however the rooting of E. saligna and E. uroglobulus clones was favored by the use of mini-tunnels. As cuttings from CMG with mini-tunnels are superior morphological quality, considering characteristics such as root dry mass and leaf area. Therefore, the use of mini-tunnels CMG is indicated for the winter in southern Brazil, as it improves the quality of the mini-stumps and seedlings, in addition to offering gains in rooting.